THE USAGE OF GROUP INTERACTIVE TEACHING METHODS IN THE LEARNING OF PHARMACEUTICAL CHEMISTRY - Velyka, Alla; Kropelnytska, Yulia; Garvasiuk, Oleksandra (SWorldJournal, 2025)
Modern education aims to train highly qualified specialists capable of responding quickly to societal challenges and being competitive in the labor market. This requires not only the acquisition of new knowledge, skills, and abilities but also the formati